From Assessment To Empowerment: Using Student Feedback To Shape EFL Teaching - Putu Sri Darmayanti; Ni Made Sri Rahayu; I Putu Agus Endra Susanta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the impact of student feedback in shaping English as a Foreign Language (EFL) instruction within a university classroom setting. Grounded in action research methodology, the investigation analyzes qualitative data gathered through weekly anonymous feedback forms, reflective teaching journals, and semi-structured interviews. Findings reveal that when student input is systematically integrated into instructional decision-making, it enhances lesson clarity, increases learner engagement, and strengthens student autonomy. Participants reported feeling more empowered and motivated as their feedback led to tangible changes in teaching strategies, such as adjusted lesson pacing and the introduction of more interactive activities. The research also highlights the development of students' feedback literacy and the positive shift in classroom dynamics when learner voice is acknowledged. While challenges such as vague responses and cultural reluctance to critique authority were noted, these were addressed through scaffolding and feedback training. The study concludes that student feedback, when used as a formative practice, can be a powerful tool for creating inclusive, adaptive, and learner-centered EFL environments.